Exploring Lexical Errors of Indonesian EFL Students in Writing Recount Texts - Muhammad Hamdan Fakhrudin; Dzulfikri Dzulfikri; Mutmainah Mustofa (Journal of English Language Teaching and Linguistics, 2023)
The study aimed to examine the EFL students’ lexical errors in writing recount texts. This study employed a descriptive qualitative method involving 31 students and uses the taxonomy of James’ lexical errors in analyzing the texts. The findings revealed that there was a total of 161 lexical errors in the students’ recount writings. Likewise, it was claimed that misselection became the most frequent lexical error, with 73 errors. The next was suffix type with 35 errors and calque with 10 errors. Furthermore, the results showed that most students felt difficult to select the appropriate lexical types in writing recount texts and most of the formal errors resulted from the intralingual error. Thus, the study recommends that the teachers teach vocabulary in contexts rather than words and use English thesaurus or monolingual dictionaries to find the grammatical content, definitions, examples, spelling, or other structures. The study also recommends online lexical analyzers, drillling, and remedy as the other alternative methods of reducing lexical errors in writing.